ALI : A LIFE - JONATHAN EIG (NEW DELHI SIMON & SCHUSTER, 2017)
The first truly definitive biography of Muhammad Ali, the most iconic and significant sporting figure of the twentieth century
Keywords: MUHAMMAD ALI-BIOGRAPHY; BOXING